Qualitative and Quantitative Evaluation of Active Constituents in Callus of Lavandula angustifolia plant in Vitro (Baghdad Science Journal, 2020)
This study was conducted to describe a protocol for the callus establishing culture of Lavandula angustifolia plant and estimating their content of volatile oil. The quantity of volatile oil callus tissues was compared with that of leaves production. Callus was induced from leaf explants on Murashige and Skoog medium (MS) supplemented with Naphthalene acetic acid (NAA) and Benzyl adenine (BA) in different concentrations. Maximum callus fresh weight was obtained in the combination of 10 mg/L BA and 3 mg/L NAA which reached 18 g after four weeks. The results of this work showed that the quantity of volatile oil from the highest fresh weight callus was 6 ml compared with quantity of 18g of leaves which gave 0.5 ml. Volatile oil of leaf and callus extracts were analyzed using gas chromatography mass spectrometry method (GC-MS) which showed linoleic acid (56.61%) and oleic acid (57.93%) as main components.